2020
DOI: 10.1016/j.heliyon.2020.e05631
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of the growth-poverty-inequality trilemma in Sub-Saharan Africa and Latin American and Caribbean Countries

Abstract: To "end poverty in all its forms everywhere" and "reduce inequality within and among countries", this study aligns with the 2030 Sustainable Development Goals 1 and 10. It uniquely contributes to the growth-poverty-inequality discourse by using per capita consumption expenditure growth (poverty), Gini index (inequality) and GDP growth (economic growth). It is a comparative analysis of 58 Sub-Saharan Africa (SSA) and Latin American (LAC) countries (from 2000 to 2015) to determine whether economic growth reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 45 publications
(55 reference statements)
8
78
0
1
Order By: Relevance
“…The result showed that while inequality has a positive and significant effect on economic growth in Nigeria, poverty has an insignificant impact on economic growth. Adeleye et al (2020) carried out a comparative analysis on growth, poverty and inequality in sub-Saharan Africa, Latin America and Caribbean countries using pooled ordinary least square, fixed effects and system generalized method of moment for the period 2000 to 2015. The result of the study shows inequality growth rate increases poverty and economic growth reduces poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that while inequality has a positive and significant effect on economic growth in Nigeria, poverty has an insignificant impact on economic growth. Adeleye et al (2020) carried out a comparative analysis on growth, poverty and inequality in sub-Saharan Africa, Latin America and Caribbean countries using pooled ordinary least square, fixed effects and system generalized method of moment for the period 2000 to 2015. The result of the study shows inequality growth rate increases poverty and economic growth reduces poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trilemma of the growth-poverty-inequality study for the case of Sub-Saharan African, Latin American, and Caribbean countries shows that economic growth reduces poverty, while an increase in inequality is in line with an increase in poverty. There-fore, an increase in inequality will exacerbate the impact of economic growth on poverty (Adeleye et al 2020). Testing the growth-inequality-poverty (GIP) triangle in 16 countries with the devastating crime period of 1990-2014 using the Generalized Method of Moments (GMM) estimator panel shows a U-shaped relationship between the number of poor people and per capita income and an inverse U between income inequality and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the economic growth model, health and material human capital have an impact on economic growth (19)(20)(21)(22), and economic growth is an important means of poverty reduction (23)(24)(25)(26)(27). Therefore, the impact of health human capital on poverty through the regulation of economic growth has also been widely concerned.…”
Section: Literature Reviewmentioning
confidence: 99%